Effects of Wage and Price controls in Canada: 1975-1978 - Staudohar, Paul (Relations industrielles / Industrial Relations, 1979)
The author examines the recent Canadian experience in wage and price controls» including an analysis of these controls, the problems confronting their implementation, and certain of their results.